MNC subsidiary closures: What is the value of employees’ human capital in new jobs? - Sofka, Wolfgang; Preto, Miguel Torres; de Faria, Pedro (Journal of International Business Studies, 2014)
We investigate the consequences of MNC subsidiary closures for employees who lose their jobs. In particular, we examine the extent to which the human capital that these employees acquired while employed by the MNC influences the wages they receive in their new jobs. We propose an employee displacement model for foreign MNC subsidiaries that integrates insights from the labor economics and international business literatures. We argue that a new employer will pay higher wages when signals indicate that potential employees have valuable, foreign human capital (e.g., the closed subsidiary was highly productive by host-country standards), and lower wages when signals indicate that potential employees have highly MNC-specific human capital (e.g., the employee had a long tenure in the closed subsidiary). We provide empirical evidence based on a sample of 110,133 displaced employees of closed MNC subsidiaries in Portugal. Our data set spans the period from 2005 to 2009. Showing that MNCs create a valuable pool of human capital for host-country firms when they close subsidiaries, our findings have important implications for research and practice.